Рішення Європейського судудз прав людини про свободу асоціація у справах за участю України - Волкова Дарія Євгенівна; Волкова Дарья Евгеньевна; Volkova Dariya (My University, 2013)
The paper analyzes the decisions of the European Court of Human Rights on freedom of association in cases involving Ukraine. The article begins with a brief overview of Art. 11 "Freedom of assembly and association" of the Convention for the Protection of Human Rights and Fundamental Freedoms, 1950. Based on the content of the article and the laws of Ukraine, author analyzes Court's decision related to the practical implementation and protection of freedom of association in Ukraine. The decision on the case Koretsky and another against Ukraine, 2008, is devoted exclusively to freedom of association, while a decision on the case Trofimchuk against Ukraine, 2011, is not only about freedom of association. The freedom of association in this decision is closely connected to the freedom of peaceful assembly.
Волкова Д. Є. Рішення Європейського Суду з прав людини про свободу асоціацій у справах за участю України / Д. Є.Волкова // Держава і право. – Київ, 2013.- № 60. – С.106-111.
Keywords: свобода асоціацій; об’єднання громадян; громадські організації; статути громадських організацій; професійні спілки; свобода ассоциаций; объединения граждан; общественные организации; уставы общественных организаций; профессиональные союзы; freedom of association; citizens' associations; nongovernmental organizations; statutes of NGOs; trade unions